Multi-dimensional WAF-type schemes for model conservation laws - Toro, E. F. (Cranfield University, 1993)
We explore how the Weighted Average Flux (WAF) approach can be used to generate first and second order accurate finite volume schemes in one, two and three space dimensions. The derived schemes have multidimensional upwinding aspects and good stability properties. We construct oscillation-free methods that are second order accurate in smooth flow by making use of one-dimensional limiter functions. Some numerical results are presented.